2020
DOI: 10.5217/ir.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

Advanced neoplasia detection using chromoendoscopy and white light colonoscopy for surveillance in patients with inflammatory bowel disease

Abstract: Background/Aims: Chromoendoscopy (CE) has been shown to be superior to white light endoscopy (WLE) for neoplasia detection in inflammatory bowel disease (IBD). We aimed to compare the yield of CE and WLE for the detection of overall neoplasia and advanced neoplasia in IBD. Methods: Patients who underwent surveillance colonoscopy from 1999 to 2017 were identified from our IBD database. CE procedures were compared with their respective WLE controls in a paired comparison, and frequency of all neoplasia, advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(80 reference statements)
0
8
0
2
Order By: Relevance
“…DCE showed a higher detection of dysplasia compared to HD-WLE (17 vs. 7; p = 0.032) [40]. Even in a retrospective study by Kim et al DCE performed better than HD-WLE in dysplasia detection [41]. In this study, a paired comparison between 159 DCE and 131 WLE controls (of which 124 HD-WLE and 7 SD-WLE) was performed.…”
Section: Dce Vs Hd-wlementioning
confidence: 78%
See 2 more Smart Citations
“…DCE showed a higher detection of dysplasia compared to HD-WLE (17 vs. 7; p = 0.032) [40]. Even in a retrospective study by Kim et al DCE performed better than HD-WLE in dysplasia detection [41]. In this study, a paired comparison between 159 DCE and 131 WLE controls (of which 124 HD-WLE and 7 SD-WLE) was performed.…”
Section: Dce Vs Hd-wlementioning
confidence: 78%
“…The overall neoplasia detection rate was 40.9% in the DCE group and 23.7% in WLE (p = 0.002). Interestingly, these results did not change significantly even after excluding the 7 SD-WLE procedures [41]. Similarly, another retrospective study conducted by Sekra et al [42] showed that DCE with targeted biopsies was associated with a higher nonpolypoid dysplasia detection rate compared to HD-WLE.…”
Section: Dce Vs Hd-wlementioning
confidence: 83%
See 1 more Smart Citation
“…Strictureplasty should not be used in large bowel because the risk of malignization. Chronic inflammation is a risk factor for colon cancer and dysplasia is considered to be the precursor of most colorectal cancer in IBD patients [43].…”
Section: Colonic Diseasementioning
confidence: 99%
“…We screen and variably surveille for Barrett’s esophagus and undertake or refer patients to experienced colleagues for endoscopic mucosal resection or endoscopic submucosal dissection with finding of high-grade dysplasia and high-risk patients with superficial malignancy 22 23 24 25 26 . We recognize that chromo-endoscopy finds more dysplasia with fewer biopsies then white light endoscopy with or without the ability to magnify the image or filter the wavelength, but without formal societal guidelines, it is the minority of endoscopists who utilize it in screening patients with inflammatory bowel disease 27 28 29 . However, there are guidelines to screen for gastric malignancy 30 , to perform and interpret capsule endoscopy 31 appropriately, and about the appropriate application of endoscopic ultrasound 32 , as well as dozens of other endoscopic procedures.…”
mentioning
confidence: 99%